2011
DOI: 10.1161/circulationaha.110.983536
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cardiac Rehabilitation on Mortality and Cardiovascular Events After Percutaneous Coronary Intervention in the Community

Abstract: Background-Although numerous studies have reported that cardiac rehabilitation (CR) is associated with reduced mortality after myocardial infarction, less is known about its association with mortality after percutaneous coronary intervention. Methods and Results-We performed a retrospective analysis of data from a prospectively collected registry of 2395 consecutive patients who underwent percutaneous coronary intervention in Olmsted County, Minnesota, from 1994 to 2008. The association of CR with all-cause mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
230
0
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(264 citation statements)
references
References 42 publications
4
230
0
12
Order By: Relevance
“…Meta‐analyses suggested that CR participation can reduce all‐cause mortality by 15% to 28% for patients with MI4, 37, 38, 39 and 45% to 47% for patients with percutaneous coronary intervention 40. The effect was estimated to be comparable to improvements associated with aspirin, β‐blocker, angiotensin‐converting enzyme inhibitor, statin, and anticoagulant therapy 5, 41, 42, 43.…”
Section: Discussionmentioning
confidence: 99%
“…Meta‐analyses suggested that CR participation can reduce all‐cause mortality by 15% to 28% for patients with MI4, 37, 38, 39 and 45% to 47% for patients with percutaneous coronary intervention 40. The effect was estimated to be comparable to improvements associated with aspirin, β‐blocker, angiotensin‐converting enzyme inhibitor, statin, and anticoagulant therapy 5, 41, 42, 43.…”
Section: Discussionmentioning
confidence: 99%
“…[301][302][303][304] CR after AMI is a Class I recommendation in evidence-based guidelines. 57,216,217,305,306 Although referral to CR is designated as a performance measure of healthcare quality after AMI, 307,308 CR has failed to reach >80% of eligible women in the last 3 decades.…”
Section: Nonpharmacological Treatment Cardiac Rehabilitation Referralmentioning
confidence: 99%
“…Regular physical activity reduces the risk of cardiovascular events among patients with IHD 1, 3. For example, participation in exercise‐based cardiac rehabilitation has been demonstrated to reduce mortality by up to 30% 4, 5, 6, 7, 8, 9. However, the majority of eligible patients do not participate in a cardiac rehabilitation program 8, 10, 11.…”
mentioning
confidence: 99%